Clinical and genetic characterization of pituitary gigantism: an international collaborative study in 208 patients - Liliya Rostomyan; Adrian Daly; Patrick Pétrossians; E. Nachev; Anurag Lila; Anne-Lise Lecoq; Beatriz Lecumberri; Giampaolo Trivellin; Roberto Salvatori; Andreas Moraitis; I. M. Holdaway; Dianne J Kranenburg - van Klaveren; et al. (2015)
Despite being a classical growth disorder, pituitary gigantism has not been studied previously in a standardized way. We performed a retrospective, multicenter, international study to characterize a large series of pituitary gigantism patients. We included 208 patients (163 males; 78.4%) with growth hormone excess and a current/previous abnormal growth velocity for age or final height >2 s.d. above country normal means. The median onset of rapid growth was 13 years and occurred significantly earlier in females than in males; pituitary adenomas were diagnosed earlier in females than males (15.8 vs 21.5 years respectively). Adenomas were ≥10 mm (i.e., macroadenomas) in 84%, of which extrasellar extension occurred in 77% and invasion in 54%. GH/IGF1 control was achieved in 39% during long-term follow-up. Final height was greater in younger onset patients, with larger tumors and higher GH levels. Later disease control was associated with a greater difference from mid-parental height ( r =0.23, P =0.02). AIP mutations occurred in 29%; microduplication at Xq26.3 – X-linked acrogigantism (X-LAG) – occurred in two familial isolated pituitary adenoma kindreds and in ten sporadic patients. Tumor size was not different in X-LAG, AIP mutated and genetically negative patient groups. AIP- mutated and X-LAG patients were significantly younger at onset and diagnosis, but disease control was worse in genetically negative cases. Pituitary gigantism patients are characterized by male predominance and large tumors that are difficult to control. Treatment delay increases final height and symptom burden. AIP mutations and X-LAG explain many cases, but no genetic etiology is seen in >50% of cases.